THE DEVELOPMENT OF LOCAL WISDOM-BASED REGIONAL LEADING PRODUCT: A PROPOSED IDEA - Lina Anatan (Balai Besar Kerajinan dan Batik, 2021)
This study aims to explore the problems faced by Batik Sekar Putri and offer the ideas to develop the business as one of the leading products in Cimahi City. Based on the interview, it can be identified several main problems faced, include: limited human resources creativity due to the difficulty of getting employees with some required expertise; lack of capital to purchase production equipment such as batik’s stamp and quality management that have not been fully implemented; there is no separation between corporate and personal finances; the limitations in the use of information technology as a promotional medium cause financial problems, especially when there is little or no demand or sales; efforts to develop heritage tourism through mini museums that cannot be developed due to limited funds; and organizational management which is still very simple. Efforts to develop business partners as one of the regional superior products are more focused on aspects of SMEs empowerment including mentoring and development. Assistance is carried out by providing knowledge transfer in the form of theory and training related to efforts to overcome the problems faced, while development is related to business transformation in digital form which is currently of minimal use. Through this empowerment, it is expected that the performance and competitiveness of partners can be improved so that they can be made as one of the regional superior products based on local wisdom.